Prevalence of trachoma in school children in the Marajó Archipelago, Brazilian Amazon, and the impact of the introduction of educational and preventive measures on the disease over eight years. - Joana Favacho; Antonio José Ledo Alves da Cunha; Samara Tatielle Monteiro Gomes; Felipe Bonfim Freitas; Maria Alice Freitas Queiroz; Antonio Carlos Rosário Vallinoto; Ricardo Ishak; Marluísa de Oliveira Guimarães Ishak (Public Library of Science (PLoS), 2018)
Trachoma is the leading infectious cause of blindness in the world and is associated with precarious living conditions in developing countries. The aim of the present study was to evaluate the prevalence of trachoma in three municipalities of the Marajó Archipelago, located in the state of Pará, Brazil. In 2008, 2,054 schoolchildren from the public primary school system of the urban area of the region and their communicants were clinically examined; in 2016, 1,502 schoolchildren were examined. The positive cases seen during the clinical evaluation were confirmed by direct immunofluorescence (DIF) laboratory tests. The presence of antibodies against the genus Chlamydia was evaluated by indirect immunofluorescence (IIF), and the serotypes were determined by microimmunofluorescence (MIF). In 2008, the prevalence of trachoma among schoolchildren was 3.4% (69 cases) and it was more frequent in children between six and nine years of age and in females; among the communicants, a prevalence of 16.5% was observed. In 2016, three cases of trachoma were diagnosed (prevalence of 0.2%), found only in the municipality of Soure. The results of the present study showed that in 2008, trachoma had a low prevalence (3.4%) among schoolchildren in the urban area of Marajó Archipelago; eight years after the first evaluation and the introduction of control and prevention measures (SAFE strategy), there was a drastic reduction in the number of cases (0.2%), demonstrating the need for constant monitoring and effective measures for the elimination of trachoma.